ANALISIS PENGARUH VARIASI SUDUT ELEKTRODA E7018 TERHADAP KEKUATAN TARIK SAMBUNGAN LAS SMAW PADA BAJA JIS G3101 SS400 UNTUK KOMPONEN RANGKA ATAP KOPERASI MERAH PUTIH - Budi Santoso; Muhammad Hanif Abu Zakki (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
This study aims to analyze the effect of E7018 electrode angle variations at 60°, 75°, and 90° on the tensile strength of SMAW welded joints on JIS G3101 SS400 steel applied as roof frame components of the Koperasi Merah Putih. SS400 steel is one of the most widely used structural materials in building construction due to its adequate mechanical properties and ease of welding. The SMAW process was selected for its flexibility and efficiency in field applications. Welding was performed using an E7018 electrode with a diameter of 3.2 mm at a constant current of 100 A, V-groove 45° joint preparation, 1G flat position, and a material thickness of 6 mm. The research method employed is a quantitative experimental approach with tensile testing conducted in accordance with the ASTM E8 standard. Each electrode angle variation used three specimens, resulting in a total of nine test specimens that were consistently prepared and tested. The test results indicate that the 75° electrode angle produced the highest tensile strength of 429.33 MPa, followed by the 90° angle at 388.00 MPa, and the lowest value recorded at the 60° angle with 370.33 MPa. These differences in tensile strength values are attributed to the influence of electrode angle on the quality of weld penetration and fusion formed during the welding process. The 75° electrode angle proved to produce the most optimal penetration and fusion, and is therefore recommended as the best welding parameter for SS400 steel roof frame components using the SMAW process.